Geo-environmental Hazards in the Coastal Regions of West Bengal, India - Patra, Subhankar (Emerging Issues in Environment, Geography and Earth Science Vol. 8, 2024)
The coastal zone is the area of interaction between land and sea. It includes both terrestrial as well as marine resources, which may be renewable as well as non-renewable. This paper assessed and cartographically analysed the impact of recent coastal geo-environmental hazards on coastal resources and also human life. Cyclonic storms, high wave action, tidal bore, coastal flood and also coastal erosion are the main geo-environmental hazards over the Bay of Bengal coastal area, especially the Kanthi coastal tract of west Bengal. Intensive visits to the study area, an extensive literature survey, and experimental documentary analysis were the three key measures in preparing this paper and conducting this study. Digha - Junput coastal tract over which this study was concentrated is a part of the Kanthi coastal plain of Purba Medinipur, West Bengal, India. Sea surface temperature over a period of 50 years was observed through this study to be changing up to the magnitude of about 0.019oC/year over the Bay of Bengal between the period from 1972 to 2005. As a result, the accelerated trend for the genesis and favourable conditions for the severe cyclones of 1978, 1988, 1989, 1995, 2009, 2010, 2011, 2012 and 2013. The local sea level has risen, on average 15 cm/last 3 decades. High wave action and coastal floods due to cyclonic storms and also high rainfall during the monsoon seasons (In record and evidence of the highest sea gauge during the last 30 years generally increasing which is relatively 2 m to 3 m) have been affected to coastal environment. On the other hand, coastal erosion is another geomorphic hazard identified in this study to be due to high wave action during the cyclonic period and also the monsoonal season. As a result, about 25 m to 50 m/year of coastal land has been eroded at Digha-Shankarpur and adjoining coastal tract. For this reason, the popular and famous beach tourism spot Digha-Mandarmoni of West Bengal has been extremely affected and also destroyed the gentle sea beach in recent times. Agricultural crops mainly food grains, vegetables, cashew nuts, betelvine and many commercial crops and horticulture have been affected by the geo-environmental hazards of this area. So, resource depletion and resource crisis are the main problems in this area in recent times. On the other hand, numerous geo-environmental hazards throughout the year have attacked the coastal inhabitants. For this reason, the coastal people of the Kanthi coastal area have been suffering continually during the last 50 years. As a result, thousands of people are environmental refugees. The situation can be tackled by enhancing risk preparedness and the adaptive capacity of vulnerable communities. So, it is right for the planning of coastal zone management by the proper and cartographic techniques.